Dissecting cholesterol and phytosterol biosynthesis via mutants and inhibitors. (15th September 2020) - De Vriese, Kjell; Pollier, Jacob; Goossens, Alain; Beeckman, Tom; Vanneste, Steffen
Abstract : The complexity and diversification of sterol biosynthesis in the green lineage make it difficult to manipulate plant sterol biosynthesis via currently available small molecule inhibitors. Abstract: Plants stand out among eukaryotes due to the large variety of sterols and sterol derivatives that they can produce. These metabolites not only serve as critical determinants of membrane structures, but also act as signaling molecules, as growth-regulating hormones, or as modulators of enzyme activities. Therefore, it is critical to understand the wiring of the biosynthetic pathways by which plants generate these distinct sterols, to allow their manipulation and to dissect their precise physiological roles. Here, we review the complexity and variation of the biosynthetic routes of the most abundant phytosterols and cholesterol in the green lineage and how different enzymes in these pathways are conserved and diverged from humans, yeast, and even bacteria. Many enzymatic steps show a deep evolutionary conservation, while others are executed by completely different enzymes. This has important implications for the use and specificity of available human and yeast sterol biosynthesis inhibitors in plants, and argues for the development of plant-tailored inhibitors of sterol biosynthesis.